Inductor-Less Low-Power Low-Voltage Cross-Coupled Regulated-Cascode Transimpedance Amplifier Circuit in CMOS Technology - Behnam Abdollahi; Baset Mesgari; Saeed Saeedi; Zahra Sohrabi; Bernhard Goll; Horst Zimmermann (IEEE Access, 2024)
This paper presents an inductor-less low-power low-voltage cross-coupled regulated cascode (LV CC-RGC) transimpedance amplifier (TIA) design topology with a negative resistance in addition to the traditional gm-boosting approach. Combining the above techniques leads to enhanced design flexibility without needing an on-chip inductor and extra power consumption. It is particularly beneficial as well when the capacitance of a large photodiode (PD) is located at the TIA input. The TIA is implemented in $0.35~μ $ m CMOS technology with a maximum ft of 20 GHz. Experimental results demonstrate a transimpedance gain of 60 dB $Ω $ , a 3-dB bandwidth of 1.8 GHz, and an average input-referred noise current spectral density of 9.2 pA/ $\surd $ Hz. The circuit’s power consumption and chip area are 2.2 mW and 0.004 mm2, respectively.